Kemampuan Berpikir Kreatif Matematis Ditinjau Dari Sosial Ekonomi Orang Tua Siswa - Dealita, Nur; Yusmin, Edy; Hamdani (Polinomial : Jurnal Pendidikan Matematika, 2025)
Creative thinking skills in mathematics play an important role in students' learning development. This study aims to understand how students at SMK Negeri 1 Jawai Selatan demonstrate their mathematical creative thinking skills, especially when viewed from the socioeconomic background of their parents. The focus of this research is not only on the results of these abilities, but also on the thinking process that occurs, both in students who come from families with low and high economic conditions. The research was conducted using a descriptive qualitative approach, involving six students from class XI TKJ 3 who were selected based on variations in mathematical creative thinking ability as well as high, medium, and low parental socioeconomic levels. Data were collected through various instruments, both tests and non-tests such as questionnaires and interviews. Data analysis refers to the Miles and Huberman model, which includes the stages of data presentation, data reduction, and conclusion drawing. The results showed that students who come from families with better socioeconomic conditions tend to have higher mathematical creative thinking skills. Students with higher parents' socioeconomic status usually have the ability to identify problems, think about and get ideas from various sources, but they cannot find unique ideas to solve problems.